The Continuous Challenge of Diagnosing patients with Fabry disease in Argentina: Genotype, Experiences, Anecdotes, and New Learnings - Rozenfeld, Paula Adriana (2015)
The lysosomal storage disorder Fabry disease (FD) is caused by pathogenic mutations in the α-galactosidase A gene, localized in X chromosome. Deficient enzymatic activity of the product of this gene, the lysosomal hydrolase α-galactosidase A, leads to accumulation of its substrate globotriaosylceramide. Diagnosis of FD starts with clinical suspicion followed by confirmatory laboratory testing. The aim of this work is to report the 14 years’ experience and learnings in the diagnosis of patients with Fabry disease in Argentina from a specialized lysosomal diseases diagnosis laboratory and to report the genotype characterization of the 25 families from Argentina with FD detected by us.